HCN2 channels account for mechanical (but not heat) hyperalgesia during long-standing inflammation - Schnorr, Sabine; Eberhardt, Mirjam; Kistner, Katrin; Rajab, Hamsa; Kaesser, Johannes; Heß, Andreas; Reeh, Peter; Ludwig, Andreas; Herrmann, Stefan (Pain, 2014)
There is emerging evidence that hyperpolarization-activated cation (HCN) channels are involved in the development of pathological pain, including allodynia and hyperalgesia. Mice lacking the HCN isoform 2 display reduced heat but unchanged mechanical pain behavior, as recently shown in preclinical models of acute inflammatory pain. However, the impact of HCN2 to chronic pain conditions is less clear and has not been examined so far. In this report, we study the role of HCN2 in the complete Freund's adjuvant inflammation model reflecting chronic pain conditions. We used sensory neuron-specific as well as inducible global HCN2 mutants analyzing pain behavior in persistent inflammation and complemented this by region-specific administration of an HCN channel blocker. Our results demonstrate that the absence of HCN2 in primary sensory neurons reduces tactile hypersensitivity in chronic inflammatory conditions but leaves heat hypersensitivity unaffected. This result is in remarkable contrast to the recently described role of HCN2 in acute inflammatory conditions. We show that chronic inflammation results in an increased expression of HCN2 and causes sensitization in peripheral and spinal terminals of the pain transduction pathway. The contribution of HCN2 to peripheral sensitization mechanisms was further supported by single-fiber recordings from isolated skin-nerve preparations and by conduction velocity measurements of saphenous nerve preparations. Global HCN2 mutants revealed that heat hypersensitivity-unaffected in peripheral HCN2 mutants-was diminished by the additional disruption of central HCN2 channels, suggesting that thermal hyperalgesia under chronic inflammatory conditions is mediated by HCN2 channels beyond primary sensory afferents.
EVALuna2:2422